Promoting Competitiveness in Ireland - 25 Years On - Dermot P. Coates; Linda Kane (National Competitiveness and Productivity Council (NCPC), 2022)
This year marks the 25th Anniversary of the establishment of the National Competitiveness Council, recently renamed the National Competitiveness and Productivity Council to reflect its new mandate. The Council reports to the Taoiseach and the Government, through the Minister for Enterprise, Trade and Employment, on key competitiveness and productivity issues facing the Irish economy and offers recommendations on policy actions required to enhance Ireland's competitive position and productivity performance. Each year the Council's Annual Report - Ireland's Competitiveness Challenge - identifies key priority areas requiring reform. The areas prioritised reflect the different stages of the economic cycle as well as structural matters such as education and skills; infrastructure; research, development, and innovation; and business costs. The Council will continue to ensure a strategic focus on the competitiveness of the economy in the face of increased global and technological changes, drawing on research evidence and expertise from the business, policy, and academic communities, and from the social partners.
Keywords: 330